Qodiyyatu al-Suluk wa al-Jadzb ‘inda Ibn ‘Atha’illah al-Sakandari - Moh Isom Mudin (Universitas Darussalam Gontor, 2017)
This paper discusses about the theory of jadzb and suluk according to Ibn Atha’Allah al-Sakandari. A discussion of this theory is still rarely done by researchers of tasawwuf. In fact, this discussion is very important as part of the main goals of the Sufis, namely makrifat billah. For this reason, this study shows its significance. Using sufistic analysis, this study concluded that Ibn Ata’ Allah is one of Sufis that explore these two concepts more deeply, especially on the aspect of jadzb. Suluk is a normal way in achieving ma’rifat, while jadzb is a special way, namely by way of a “direct pull”. The first runs by “taraqqy” and the second one with “tadally”. For him, the Jadzb is more important than the suluk, because they may get to know God faster than the suluk. Jadzb gets “anwar mujawah” and suluk needs “anwar tawajjuh”. Roads of suluk and jadzb are representation of two levels of Ihsan. Suluk can be done by anyone so that it can be applied in society. Not so with Jadzb, for the researchers is difficult to apply to the public or anyone who wants to dive into the world of sufism.